2017
DOI: 10.1590/1518-8345.1535.2901
|View full text |Cite
|
Sign up to set email alerts
|

Association between domestic violence and women's quality of life

Abstract: Objective: to analyze the association between domestic violence against women and quality of life. Method: a cross-sectional population-based household survey conducted with women 18 years and older, using a stratified sample by neighborhoods. For analysis, prevalence of domestic violence and quality of life index was verified and logistic regression was used to determine associations, with a significance level of 5%. Results: 424 women who had a prevalence of domestic violence of 54.4% and a quality of life i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0
18

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 17 publications
4
23
0
18
Order By: Relevance
“…Second, the abuse by the partner occurred several times a week in half of the cases and on a daily basis for one in four respondents. The time spent cohabiting with the abuser was a mean of 6 years, which means that these circumstances could have affected the women in terms of suicide attempts, since it has been widely reported that violence has many negative consequences and causes problems for the health of the victims (Evans et al, ; Fusco & Fantuzzo, ; Lucena et al, ; Wolford‐Clevenger & Smith, ). Accordingly, suicidal behavior is more common among women victims of violence than among women who not suffered from abuse (Haarr, ; Joe et al, ; McLaughlin et al, ; Nock et al, ; Rhodes et al, ; Wolford‐Clevenger & Smith, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the abuse by the partner occurred several times a week in half of the cases and on a daily basis for one in four respondents. The time spent cohabiting with the abuser was a mean of 6 years, which means that these circumstances could have affected the women in terms of suicide attempts, since it has been widely reported that violence has many negative consequences and causes problems for the health of the victims (Evans et al, ; Fusco & Fantuzzo, ; Lucena et al, ; Wolford‐Clevenger & Smith, ). Accordingly, suicidal behavior is more common among women victims of violence than among women who not suffered from abuse (Haarr, ; Joe et al, ; McLaughlin et al, ; Nock et al, ; Rhodes et al, ; Wolford‐Clevenger & Smith, ).…”
Section: Discussionmentioning
confidence: 99%
“…Violence against women is a public health problem that affects most societies (Lucena, Vianna, Nascimento, Campos, & Oliveira, ; Winstok & Eisikovits, ). The most common type of abuse is abuse within relationships (Bott, Guedes, Ruiz‐Celis, & Mendoza, ; Yakubovich, Heron, Feder, Fraser, & Humphreys, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A violência doméstica apresenta distribuição social em todo o mundo, sendo apontada como um tipo de violência universal e praticada preeminentemente por parceiros ou pessoas muito próximas das mulheres. De acordo com dados da Organização Mundial de Saúde, em 2013, a violência contra a mulher perpetrada por parceiro íntimo apresentou uma prevalência de 30,0%, verifica-se que a violência doméstica possui associação com a qualidade de vida das mulheres (LUCENA et al, 2017).…”
Section: Contexto E Caracterização Da Violência Contra a Mulherunclassified
“…For this, social norms and cultural patterns (for both, men and women) which confirm, authorize, naturalize and trivialize male domination over women, must be combated in order to minimize or even eliminate the great differences between the genre created and maintained by a strong historical context, and which fortunately does not fit with modern society: of equal rights and for all 8 . The issue 28(2) of the JHGD brings in its bulletin publications that contemplate articles dealing with cultural aspects of the health and disease process by talking about various factors and conceptions to explain health and illness.…”
mentioning
confidence: 99%